Deep clinical phenotyping and gene expression analysis in a patient with RCBTB1-associated retinopathy. (4th May 2021) - Huang, Zhiqin; Zhang, Dan; Thompson, Jennifer A.; Jamuar, Saumya S.; Roshandel, Danial; Jennings, Luke; Mellough, Carla; Charng, Jason; Chen, Shang-Chih; McLaren, Terri L.; Lamey, Tina M.; Chelva, Enid; et al.
ABSTRACT: Background : Mutations in the RCC1 and BTB domain-containing protein 1 ( RCBTB1 ) gene have been implicated in a rare form of retinal dystrophy. Herein, we report the clinical features of a 45-year-old Singaporean-Chinese female and her presymptomatic sibling, who each possesses compound heterozygous mutations in RCBTB1 . Expression of RCBTB1 in patient-derived cells was evaluated. Materials and Methods : The natural history was documented by a series of ophthalmic examinations including electroretinography, fundus autofluorescence imaging, spectral-domain optical coherence tomography, visual field, microperimetry, and adaptive optics retinal imaging. Patient DNA was genetically analysed using a 537-gene Next Generation Sequencing panel and targeted Sanger sequencing. Expression of RCBTB1 in lymphocytes, fibroblasts, and induced pluripotent stem cells (iPSC) derived from the proband and healthy controls was characterized by quantitative PCR, Sanger sequencing, and western blotting. Results : The proband presented with left visual distortion at age 40 due to extrafoveal chorioretinal atrophy. Atrophy expanded at 1.3 (OD) and 1.0 (OS) mm 2 /year. Total macular volume declined by 0.09 (OD) and 0.13 (OS) mm 3 /year. Microperimetry demonstrated enlarging scotoma in both eyes. Generalised cone dysfunction was demonstrated by electroretinography. A retinal dystrophy panel testing revealed biallelic frameshifting mutations, c.170delG (p.Gly57Glufs*12) and c.707delA (p.Asn236Thrfs*11) in RCBTB1 . The level of RCBTB1 mRNA expression was reduced in patient-derived lymphocytes compared to controls. RCBTB1 protein was detected in control fibroblasts and iPSC but was absent in patient-derived cells. Conclusions : Atrophy expansion rate and macular volume change are feasible endpoints for monitoring RCBTB1 -associated retinopathy. We provide further functional evidence of pathogenicity for two disease-causing variants using patient-derived iPSCs.